The Early Peat Industry in Canada, 1864-1945 - Warner, Barry; Buteau, Pierre (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary Canada is one of the leading peat-producing countries in the world although this was not always so. Commençai peat operations began in Quebec in 1864. Early attempts to commercialize fuel peat failed by the 1880s. Renewed interest in fuel peat resumed in the 1890s, mostly in Ontario and Quebec. After World War I the federal government assisted by purchasing a commercial peat plant at Alfred, Ontario. Between the wars, the industry began to move away from fuel peat production to new production of horticultural peat and other peat-based products, a trend that was greatly accelerated during and after World WarII. Indeed, World War II was a major turning point for the industry. European peat exports to the large American market were no longer economically viable, thereby creating new market opportunities for Canada. Although the industry largely began in Ontario and Quebec,British Columbia was one of the largestpeat-producing regions in the world for abrief period following World War II.Today, commercial operations are virtually non-existent in Ontario and British Columbia. Quebec, New Brunswick, Manitoba and Alberta are the primary peat-producing regions of the country. Despite early difficulties, Canada's peat industry has become a vibrant and important industry, nationally and internationally.